PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS VII SMP NEGERI 3 SINABOI TAHUN PELAJARAN 2015/2016 - Nurhadiyah '; Darmawati '; Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Research conducted in class VII SMPN 3 Sinaboi 2015/20156 school year to determine improving student learning outcomes with the use of media images. This research is a classroom action research conducted in two cycles of planning, execution and observation and reflection. The data collected in this study is the result of learning by assessing the absorption and mastery learning results obtained from the post-test and daily tests sisiwa. Student activity and teacher activity were measured using observation sheet.From the research results can be concluded that by using media images can improve learning outcomes IPA class VII SMPN 3 Sinaboi Academic Year 2015/2016 where absorption is obtained from the value of post-test on the first cycle, the first meeting is 75.35% (enough) and increased in the second meeting, namely 78.84% (enough). In the second cycle first meeting of 85.76% (good) and increasing at a meeting 2 to 90.76% (excellent). Mastery learning students in the first cycle that 76.07 (enough) and the second cycle increased to 8.00 (good). The average activity of students in cycle 1 meeting 1yaitu 90.00% (excellent) increased at a meeting 2 to 93.84% (excellent) danpada cycle II meeting 1 97.69% (excellent), increasing at a meeting 2 to 100 5 (excellent ). Activities teachers in the learning process in the first cycle is 85%, (good) and the second cycle was 100% (excellent).Keywords: Media Image, Learning Outcomes